2011
DOI: 10.1002/ceat.201100143
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of a Novel Water‐Soluble Cationic Polymer Containing β‐Cyclodextrin

Abstract: Allyl-b-cyclodextrin is utilized to react with dimethyl diallyl ammonium chloride and acrylamide to synthesize a novel water-soluble cationic polymer by redox free-radical polymerization. The optimum polymerization conditions are determined by the single-variable method, while the structure is characterized by Fourier transform infrared and scanning electron microscopy. In rheological experiments the polymer demonstrates superior properties compared to polyacrylamide. Interfacial tension and adsorption experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It could be seen from Fig. a that strong absorption peaks were observed at 3447, 1655, and 1402 cm −1 , which inferred that the polymer contained AM and AA structures . And the FTIR spectrum shows the characteristic absorption bands of allyl‐β‐cyclodextrin at 932 and 575 cm −1 .…”
Section: Resultsmentioning
confidence: 89%
“…It could be seen from Fig. a that strong absorption peaks were observed at 3447, 1655, and 1402 cm −1 , which inferred that the polymer contained AM and AA structures . And the FTIR spectrum shows the characteristic absorption bands of allyl‐β‐cyclodextrin at 932 and 575 cm −1 .…”
Section: Resultsmentioning
confidence: 89%
“…Polymerization conditions such as the ratio of AM and AA, content of APEG and KGM, reaction temperature, and pH were explored to get the best reaction conditions (for the details, see the Supporting Information). 44 The optimum synthetic conditions for graftcopolymer are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the optimum polymerization conditions, the effects of the ratio of AM to AA, NAE, emulsifier loading, reaction temperature, pH, and reaction time were investigated by the single‐variable method . First, we kept the loadings of NAE at 0.1 wt %, OP‐10 at 0.03 wt %, and the initiator at 0.05 wt %, and then ensuring the pH, reaction time, and monomer content as fixed values, we changed the temperature of the system to investigate the influence of the reaction temperature on polymerization by observing the apparent viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the reduction of the interfacial tension among oil, water, and rocks should be paid more attention when the polymer flooding strategy is used in an oil reservoir. However, HAWSPs cannot effectively reduce the interfacial tension among oil, water, and rocks . A large number of authors have indicated that a polymer solution adjusting a certain amount of surfactant (polymer–surfactant system) could reduce the interfacial tension significantly .…”
Section: Introductionmentioning
confidence: 99%